Desenvolvimento e produtividade do trigo em função da inoculação de bactérias promotoras do crescimento vegetal - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Wheat represents the most important winter crop of southern Brazil, because it is characterized as the staple food of the population. The nutrient that most limits wheat productivity is nitrogen (N), therefore, the practice of nitrogen fertilization is common and responsible for the high cost of agricultural production, besides being a considerable source of environmental contamination. In order to reduce the use of chemical fertilizers, a promising alternative is the use of Plant Growth Promoting Bacteria (PGPB), which have the benefits of biological nitrogen fixation (BNF), nutrient solubilization, phytohormone production, pathogenic activity and tolerance to abiotic stresses. In this sense, the present work had the objective of evaluating the contribution of the inoculation of wheat seeds with PGPB in the development and productivity of the wheat crop. The experiment was conducted in Ponta Grossa (PR), under a randomized block experimental design, with six replicates. The treatments consisted of one control, two doses of nitrogen fertilization in the cover, inoculation of wheat seeds with six different strains of PGPB and a treatment with the combination of four bacterial strains. In this experiment the emergence of plants, yield components, N content in the leaves and grains and quantification of diazotrophic bacteria present in the wheat rhizosphere were evaluated. The climatic condition during the experiment affected the development and productivity of wheat, contributing to low yields and interfering with the response of plants to PGPB inoculation. However, seed inoculation with Pseudomonas sp. H2D presented the highest number of wheat plants per linear meter in the tillering phase of the crop, differing statistically from the other treatments. Although the other parameters evaluated did not show statistical difference, the results with the use of PGPB are very promising and new tests should be performed to better understand the effect of inoculation in different culture conditions.
Keywords: Fixação Biológica de Nitrogênio (FBN); quantificação de bactérias diazotróficas; estresse hídrico; Biological Nitrogen Fixation (BNF); quantification of diazotrophic bacteria; hydrical stress; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA